Letter to supporters - Birdsong, Craig, author; Carlson, Linda, author (Colorado State University. Libraries, 1999)
Thank you letter to Historic Costume & Textiles Collection supporters from Craig Birdsong and Linda Carlson regarding grants and further donations needed.
Keywords: Fashion -- History; Fashion -- Exhibitions